Model Evaluasi Kinerja Tanggung Jawab Sosial Lingkungan Perusahaan di Kota Bogor - Wicaksono, Arif; Sofiah, Syarifah; Mashudi, Rudy; Badri, Lusi N; Safitri, Ratu D; Hidayati, Oni; Dewi, Irma Arlini; Susetyo, Budi (Jurnal Manajemen, 2022)
Corporate Social Responsibility (CSR) is a critical partnership potential in regional development. This potential is currently not too significant in its role and contribution to growth in Bogor, considering that the number is still limited. The TJSLP Secretariat encourages the participation of all parties through the preparation of a mechanism for submitting community TJSLP to the company. The purpose of this research is to develop a model for evaluating CSRs performance, which can be used as a basis for making decisions for the recommendations of the Bogor City government to corporate partners who have CSR programs. The evaluation model uses the PROMETHEE (Preference Ranking Organization Method for Enrichment Evaluation) method to see the feasibility of the proposal with several criteria, namely the suitability of the program with the RPJMD (K1), activity category (K2), and activity costs (K3). The research resulted in a weighted value of K1=0.50, K2=0.33, K3=0.17. That look the ranking of the most appropriate in terms of the policy is Proposal B (religious), G (health), C (spiritual), H (health), A ( health), K (sports), J (education), D (economy), E (economy), I (environment), F (background). The results of sensitivity analysis, Spearman’s Rho correlation coefficient of 0.97, between the results of the PROMETHEE ranking before and after the change in the weight of the criteria indicate high consistency, which is far from subjectivity. This TJSLP performance evaluation model is helpful for the TJSLP secretariat to evaluate the implementation of the CSR program in Bogor City.